Cartography and Epidemiological Study of Leishmaniasis Disease in Sefrou Province (2007–2010), Central North of Morocco. (15th April 2020) - Talbi, Fatima Zahra; El Khayyat, Fatiha; El Omari, Hajar; Maniar, Saâd; Fadil, Mouhcine; Taroq, Amal; Idrissi, Abdellatif Janati; El Ouali Lalami, Abdelhakim
Abstract : Increasing cases of leishmaniasis disease have been reported during recent years in Sefrou Province, Central North of Morocco. This study presents the epidemiological profile of the provincial population, aims at analyzing the epidemiological profile, and in particular, spatiotemporal follow-up of all cases of leishmaniasis. It is a retrospective analysis of leishmaniasis cases recorded between 2007 and 2010. The data were analyzed by SPSS software (version 20). Over a four-year period, from 2007 to 2010, there were 62 cases of leishmaniasis, 93.12% of cases of cutaneous leishmaniasis and 6.87% of visceral leishmaniasis. The case number of leishmaniasis in the Province of Sefrou varies between 0.165% and 0.0018%. For each type of leishmaniasis, the female sex was the most affected compared to the male sex. This difference cannot be considered statistically significant ( χ 2 = 0.083, p value = 0.77). For cutaneous leishmaniasis, all age groups were affected with a large percentage: patients aged 0–9 years with 63.11% followed by the age group [10–19] with 24.18%. Visceral leishmaniasis mainly has affected the infant population [0–9] with 83.33%. We have not observed any association between the age classes and the leishmaniasis type ( χ 2 = 6.20, p value = 0.4). From a spatial point of view, the majority of cases of leishmaniasis was reported in El Menzel region (67 cases) followed by Sefrou (64 cases) and Tazouta (38 cases). There is a statistically significant relationship between the type of leishmaniasis and the studied regions ( χ 2 = 52; p value <0.001). The study of the epidemiological profile of leishmaniasis cases may be useful in enlightening health authorities to develop screening, treatment, and control strategies to reduce the incidence rate of the disease. Other research studies can be conducted to the dynamics of the vectors of sandflies and their ecology.